2008
DOI: 10.1088/0957-4484/19/20/205201
|View full text |Cite
|
Sign up to set email alerts
|

Auger quenching-based modulation of electroluminescence from ion-implanted silicon nanocrystals

Abstract: Abstract. We describe high-speed control of light from silicon nanocrystals under electrical excitation. The nanocrystals are fabricated by ion implantation of Si + in the 15-nm-thick gate oxide of a field effect transistor at 6.5 keV. A characteristic readpeaked electroluminescence is obtained either by DC or AC gate excitation. However, AC gate excitation it is found to have a frequency response that is limited by the radiative lifetimes of silicon nanocrystals, which make impossible the direct modulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…It is observed that the EL increases significantly as the frequency increases, it reaches a maximum and then it decreases. In the literature, [1][2][3][4][5] this increase in EL is attributed to an efficiency increase while the decrease, at higher frequencies, is attributed to the Auger suppression of EL due to the finite exciton recombination lifetime.…”
Section: Power Efficiency Estimation Of Silicon Nanocrystals Based LImentioning
confidence: 98%
See 2 more Smart Citations
“…It is observed that the EL increases significantly as the frequency increases, it reaches a maximum and then it decreases. In the literature, [1][2][3][4][5] this increase in EL is attributed to an efficiency increase while the decrease, at higher frequencies, is attributed to the Auger suppression of EL due to the finite exciton recombination lifetime.…”
Section: Power Efficiency Estimation Of Silicon Nanocrystals Based LImentioning
confidence: 98%
“…Marconi, 1,a͒ A. Anopchenko, 1 G. Pucker, 2 The power efficiency of silicon nanocrystal light-emitting devices is studied in alternating current ͑ac͒ regime. An experimental method based on impedance spectroscopy is proposed.…”
Section: Power Efficiency Estimation Of Silicon Nanocrystals Based LImentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, it is clearly observed that the charge transport in both directions is increased as thickness is decreased. According to I-V curves, the mechanism of carrier injection through the SRO in devices may involve contributions of direct tunneling and the typical exponential behavior of the Fowler-Nordheim tunneling [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear optical properties of Si-nc have been extensively studied in recent years, in particular to facilitate applications such as light modulation and amplification [3][4][5]. For their fabrication, several approaches have been widely employed, such as laser ablation [6], ion implantation [7], cosputtering [8], evaporation [9,10], plasma enhanced or low pressure chemical vapor deposition (PECVD and LPCVD, respectively) [11][12][13].…”
mentioning
confidence: 99%